Job Satisfaction and Associated Factors among Healthcare Workers at King Fahad University Hospital in Al-Khobar - Alali, Maram Habib Hussain (Journal of medical and pharmaceutical sciences, 2023)
Objectives: The current study aimed to assess the levels of job satisfaction and associated factors among healthcare workers at King Fahad University Hospital in Al Khobar. Methodology: A cross-sectional study targeting healthcare workers at King Fahad University Hospital was conducted from October to December 2022. The research population consists of all 2000 healthcare workers at King Fahad University Hospital in Al Khobar. A total of 400 questionnaires were distributed and collected. After incomplete questionnaires were excluded, 332 remained to be analyzed. Results: The participants reported high job satisfaction, as indicated by the total mean score for all questionnaire items of 4.39. Furthermore, the factors influencing job satisfaction, ordered from the highest to the lowest percentage, are as follows: work physical environment (89.1%), working hours (88.4%), work culture environment (86.6%), pay benefits package (85.6%), patient satisfaction (84.4%), stress management (83.8%), quality of care provided (81.6%), and other factors (1.9%). The variables of work experience, specialty, educational level, gender, and age affected job satisfaction among healthcare workers. Conclusion: This study revealed a high level of satisfaction among healthcare workers at King Fahad University Hospital and suggests that healthcare workers should be given more organizational support, incentive benefits, and flexible work shifts to enhance their job satisfaction.